Percepción de la calidad de atención en servicios de salud y automedicación en estudiantes de enfermería - Chero Arge, Roberto Brander (2012)
The present quantitative, descriptive and correlational type study, of transverse court, was realized in the National University of Trujillo - Headquarters Fence in Jequetepeque whose general aim was to determine the relation that exists between the perceptions of the quality of attention of the services of health with the automedication in infirmary students. The sample universe was constituted by 159 students who fulfilled the criteria of incorporation of the investigation. For obtain the necessary information the instrument was in use "Automedication and perception of the attention of health quality services". The information was processed by the statistical program SPSS by Windows version 19 the results are presented in simple tables and of double entry besides graphs, coming to the conclusions the percentages of the perception of the attention health quality services 57 %, 42.5 % and 0.6 % according to the ranges of bad, regular and good respectively. The percentages of medication in the nursing students 57.9 % students if self-medication and the 42.1 % students who not medicate themselves. It was determined that there is highly significant relation between both variables on having applied the statistical test of Chi-cuadrado: x2=10.09 p=0.000. On that way, the results show that the bad perception of the attention of health quality services influences the faculty infirmary student’s decision of automedicate themselves.